Citizen journalism and Hip-hop in the arab world: a case study (Mantichora. Italian Journal of Performance Studies, 2020)
This paper is the result of work in progress designed to examine the relationship between forms of language appropriation and acts of identity involved in two different forms of globalization, i.e. blogging and citizen journalism on the one hand, and hip-hop in English on the other. Its goal is to show that both bloggers/citizen journalists and hip-hop musicians perform an act of identity through their specific use of language, in this case English as a language of international communication, and it is through this tool that they try to stand out as part of a global community made up of local identities.